Math, asked by anshika0333, 9 months ago

12. If + cot = , then prove that cos = 2 −1 2+1

Answers

Answered by Anonymous
5

Answer:

\huge\underline\bold\red{Answer!!}

<font color="blue">Cosec theta + cot theta = P (given) we know, cosec² theta - cot² theta = 1 (cosec theta + cot theta)( cosec theta - cot theta)= 1 (cosec theta - cot theta) × P = 1 ( cosec theta - cot theta) = 1/P Let's solve (i ) and (ii) cosec theta = 1+ P²/2P cot theta = P²-1/2P cot theta / cosec theta= P²-1/2P×2P/P2²+1 cos theta = P²-1/P²+1

Answered by Anonymous
14

Answer:

Cosec theta + cot theta = P (given) we know, cosec² theta - cot² theta = 1 (cosec theta + cot theta)( cosec theta - cot theta)= 1 (cosec theta - cot theta) × P = 1 ( cosec theta - cot theta) = 1/P

Let's solve (i ) and (ii) cosec theta = 1+ P²/2P cot theta = P²-1/2P cot theta / cosec theta= P²-1/2P×2P/P2²+1 cos theta = P²-1/P²+1

Hope it will be helpful ✌️

Similar questions